The theory of a many boson system with the deformed Heisenberg algebra - Vakarchuk, I.O.; Panochko, G.I. (Condensed Matter Physics, 2015)
We propose to consider nonlinear fluctuations in the theory of liquid ⁴He deforming the commutation relations between the generalized coordinates and momenta. The generalized coordinates are the coefficients of the density fluctuations of the Bose particles. The deformation parameter takes into account effects of three- and four-particle correlations in the behavior of the system. This parameter is defined from the experimental values of the elementary excitation spectrum and the structure factor extrapolated to T=0 K. The numerical estimation of the ground state energy and the Bose condensate fraction is made. The elementary exitation spectrum and the potential of interaction between the helium atoms are recovered.